Penerapan Terapi Guided Imagery Pada Tn. A Terhadap Penurunan Skala Nyeri Pada Pasien Gastritis Di Rs Ibnu Sina Makassar - Musdalifa Musdalifa; Yusrah Taqiyah; Sudarman Sudarman; H Muhajirin (Wal'afiat Hospital Journal, 2025)
Gastritis is one of the most common digestive disorders, often referred to as heartburn. This condition is characterized by inflammation of the gastric mucosa due to irritation or infection, which can lead to stomach damage if it persists. Gastritis is typically diagnosed based on clinical symptoms without histopathological examination. One non-pharmacological approach to alleviating pain caused by gastritis is Guided Imagery, a relaxation technique involving guided imagination to create positive mental images perceived by various senses. This technique aims to provide a calming effect and help reduce pain perception. This study aimed to evaluate the effectiveness of Guided Imagery in reducing pain intensity among patients with gastritis. The implementation of Guided Imagery was carried out as part of nursing interventions for patients with gastritis. The results showed that this technique effectively reduced pain levels, as indicated by a decrease in pain intensity and a reduction in expressions of discomfort, such as the absence of grimacing. Additionally, patients reported feeling more relaxed and comfortable after the therapy. In conclusion, Guided Imagery has proven to be an effective non-pharmacological method for reducing pain in gastritis patients. Given its benefits, this therapy can be recommended as part of a holistic approach to pain management for gastritis patients, particularly for those seeking to avoid or complement pharmacological treatments.